DIAGNOSTIC VALUE OF FINE NEEDLE ASPIRATION CYTOLOGY IN DIAGNOSIS OF NON-THYROIDAL NECK MASSES - Wahid, Fazal i; Rehman, Habib ur; Khan, Qaiser; Shahabi, Isteraj Khan (Journal of Postgraduate Medical Institute, 2011)
Objective: Methodology: Results: Conclusion: Fine needle aspiration cytology for non-thyroidal neck masses has equal diagnostic yield to open biopsy. The findings were TB 31%, metastatic lymph node 19%, reactive lymphadenopathy 9%, lymphoproliferative disease 11%, pleomorphic adenoma 8%, thyroglossal cyst 5%, carotid body tumour 4%, lipoma and branchial cysts were 3% each, sialolithiasis 2% and one case each of dermoid, sebaceous cyst, adenoid cystic carcinoma, Kikuchi's disease and Ewing's tumour. Correlation of FNAC with biopsy was for TB; true positive, 64.5%, true negative 29.03%, false positive 3.22%, false negative 3.22% and for metastatic lymph node true positive 57.89%, true negative 36.84%, false positive 5.26% and no case of false negative. The diagnostic yield of FNAC was for TB, accuracy, sensitivity, specificity, positive predictive value and negative predictive value were 93.54%, 95.23%, 90%, 95.23% and 90% respectively. Metastatic lymph nodes accuracy sensitivity, specificity, positive predictive value and negative predictive value were 94.73%, 100%, 87.5%, 91.66% and 100% respectively. Overall diagnostic value of FNAC in non-thyroidal neck masses with regard to accuracy, sensitivity, specificity, positive predictive value and negative predictive value were 90%, 90%, 77.42%, 90.41%, 90.41%, and 88.89% respectively. This descriptive study was conducted at the Department of ENT, Lady Reading Hospital Peshawar from January to December 2009. Hundred patients with non-thyroidal neck masses fulfilling the inclusion criteria were included in the study. Fine needle aspirations were performed by the same cytopathologist. To determine the diagnostic value of fine needle aspiration cytology in the diagnosis of nonthyroidal neck masses.